The dynamics of procalcitonin in COVID-19 patients admitted to Intensive care unit - a multi-centre cohort study in the South West of England, UK. Issue 6 (June 2021) - Williams, Philip; McWilliams, Chris; Soomro, Kamran; Harding, Irasha; Gurney, Stefan; Thomas, Matt; Albur, Maha; Martin Williams, O.
Highlights: We have undertaken a retrospective observational study describing the dynamics of PCT and CRP, including the response to antibiotic treatment, in adults with severe COVID-19 infection requiring ICU admission. Results were compared to two better-understood groups of patients from historical data, adult ICU patients with either bacteraemia or influenza. Elevated PCT in the first 48 h of admission was rare in COVID-19 patients. Where PCT was recorded it was <1.0 ng/L in 68.9% of COVID compared to 38% influenza patients. PCT was low throughout the study, or responded rapidly to antibiotics 65.4% and 82.6% of COVID-19 and influenza patients respectively. The dynamics of PCT in COVID-19 patients are consistent with a response to secondary bacterial infection and are not consistent with an inflammatory response to COVID-19 alone, and in contrast to CRP, PCT appears to be a useful biomarker in identifying COVID-19 patients with super-added bacterial.